2012
DOI: 10.1007/s00246-012-0443-0
|View full text |Cite
|
Sign up to set email alerts
|

Cor Triatiratum Dexter: A Rare Cause of Isolated Right Atrial Enlargement

Abstract: Cor triatriatum sinistrum (division of the left atrium) is a recognized clinical and surgical entity. Division of the right atrium, also known as cor triatriatum dexter, is an extremely rare congenital abnormality in which persistence of the right valve of the embryonic systemic sinus venosus divides the right atrium into two chambers. Typically, the right atrial partition is due to exaggerated fetal eustachian and thebesian valves, which together form an incomplete septum across the lower part of the atrium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…[5,17] Both lesions can lead to an increased strain on the respective atria leading to atrial dilation with atrial fibrillation. [19] As with other stenotic valvular lesions, the CT patients with restrictive membrane poorly tolerate dysrhythmias that diminish diastolic filling time (tachycardia, atrial fibrillation).…”
Section: Discussionmentioning
confidence: 99%
“…[5,17] Both lesions can lead to an increased strain on the respective atria leading to atrial dilation with atrial fibrillation. [19] As with other stenotic valvular lesions, the CT patients with restrictive membrane poorly tolerate dysrhythmias that diminish diastolic filling time (tachycardia, atrial fibrillation).…”
Section: Discussionmentioning
confidence: 99%
“…Cor triatriatum dextrum, an extremely rare form of cor triatriatum, accounting for 0.025% of all congenital heart disease. 12 It can occur as an isolated cardiac anomaly 13 or associated with other malformation of right heart structures such as pulmonary artery stenosis or atresia, pulmonary valve stenosis or atresia, hypoplastic right ventricle, tricuspid valve stenosis or atresia, atrial septal defect and Ebstein anomaly. 4,14,15 Unlike cor triatriatum sinistrum, which carries a higher mortality rate if not repaired, cor triatriatum dextrum has varying clinical manifestations depending on the degree of obstruction to venous flow ranging from asymptomatic to overt rightsided heart failure and elevated central venous pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term prognosis for an iso- lated cor-triatriatum dexter is good, but there are no reports available for cor-triatriatum dexter associated with pulmonary hypertension. In South India, a case of a divided right atrium evaluated for nonspecific symptoms and unexplained cardiomegaly with right atrial enlargement was reported [8]. Another one case of isolated cor triatriatum dexter, symptomatic for severe central cyanosis, in which the membrane was identified before surgery by means of transthoracic echocardiography alone, and successfully removed surgically at 1 month of life [9].…”
Section: Discussionmentioning
confidence: 99%